The Right of Reproduction and Its Exceptions in Vietnamese Law during the French Colonial Period - Thanh Danh, Nguyen Ngo (VNU Journal of Science: Legal Studies; Vol 41 No 2, 2025)
The copyright regime in Vietnam has undergone significant changes since the first regulations were established during the French colonial period. Although outdated, the approaches from this period retain some value for current legal research. In particular, the principles and general approaches to copyright, reproduction rights, and issues related to exceptions for reproduction rights, such as citation and private copying, can be studied to improve current legislation. This article will sequentially introduce the legal sources regarding copyright during the colonial period, the concepts of copyright and reproduction rights, as well as the limitations on reproduction rights at that time.